JD419, a Staphylococcus aureus Phage With a Unique Morphology and Broad Host Range - Feng, Tingting; Leptihn, Sebastian; Dong, Ke; Loh, Belinda; Zhang, Yan; Stefan, Melanie I.; Li, Mingyue; Guo, Xiaokui; Cui, Zelin (Frontiers in Microbiology, 2021)
Phage therapy represents a possible treatment option to cure infections caused by multidrug-resistant bacteria, including methicillin and vancomycin-resistant Staphylococcus aureus, to which most antibiotics have become ineffective. In the present study, we report the isolation and complete characterization of a novel phage named JD219 exhibiting a broad host range able to infect 61 of 138 clinical strains of S. aureus tested, which included MRSA strains as well. The phage JD419 exhibits a unique morphology with an elongated capsid and a flexible tail. To evaluate the potential of JD419 to be used as a therapeutic phage, we tested the ability of the phage particles to remain infectious after treatment exceeding physiological pH or temperature. The activity was retained at pH values of 6.0-8.0 and below 50°C. As phages contain virulence genes, JD419's complete genome was sequenced. The 45509 bp genome contains a predicted 65 ORFs, none of which show homology to any known virulence or antibiotic resistance genes. Genome analysis indicates that JD419 is a temperate phage, despite observing rapid replication and lysis host strains. Following the recent advances in synthetic biology, JD419 can be modified by gene engineering to remove prophage-related genes, preventing potential lysogeny, in order to be deployed as a therapeutic phage.